Cognitive improvement and prefrontal network interactions in individuals with remitted bipolar disorder after transcranial infrared laser stimulation - Douglas W. Barrett; Roger E. Davis; Jennifer E. Siegel-Ramsay; Amy Bichlmeier; Jorge R. C. Almeida; F. Gonzalez-Lima (Frontiers in Psychiatry)
BackgroundConverging evidence suggests that bipolar disorder (BD) involves mitochondrial dysfunction and prefrontal cortex (PFC) hypometabolism associated with cognitive impairment, which persists in remitted BD individuals. Transcranial infrared laser stimulation (TILS) provides safe, non-invasive brain stimulation that enhances PFC metabolism via photobiomodulation of mitochondrial respiration and tissue oxygenation. We tested the hypothesis that the neurocognitive deficits found in BD may be ameliorated by TILS treatments.MethodsThis is the first study to explore neurocognitive effects of repeated TILS administration in BD. Using an open-label design, 29 individuals with remitted BD received six weekly TILS treatments. Working memory and attention were assessed with trail-making and 2-back tasks sensitive to TILS cognitive effects in individuals with BD. Changes in PFC network interactions were measured with functional near-infrared spectroscopy (fNIRS) because this method can measure TILS effects on oxygen metabolism in the PFC of individuals with BD.ResultsParticipants reported no adverse effects from treatment, confirming the safety of this intervention in individuals with BD. Cognitive test results showed that in people with remitted BD, TILS was effective at improving cognition, i.e., enhanced speed and accuracy in tasks reflecting cognitive flexibility, working memory, and attentional control. Antipsychotic medication improved TILS cognitive effects. The fNIRS results showed a significant reduction in PFC network correlations of oxygenated hemoglobin changes driven by cognitive task performance. The right-hemisphere frontopolar cortex showed greater TILS effects than its left-hemisphere counterpart.ConclusionsRepeated TILS is a safe intervention to improve cognition in people with remitted BD. Continued antipsychotic medication may have contributed to the cognitive improvement. To confirm TILS efficacy, a sham-controlled, double-blinded randomized trial is needed.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT05354895.